Evolutionary engineering of interspecies cooperation: Investigating Saccharomyces cerevisiae and Lactobacillus plantarum interactions in a synthetic ecological environment - Du Toit, Sandra Christine (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhDAgric)--Stellenbosch University, 2021.